2017
DOI: 10.1186/s12888-017-1476-y
|View full text |Cite
|
Sign up to set email alerts
|

Jump step - a community based participatory approach to physical activity & mental wellness

Abstract: BackgroundThere is a physical inactivity pandemic around the world despite the known benefits of engaging in physical activity. This is true for individuals who would receive notable benefits from physical activity, in particular those with mood disorders. In this study, we explored the factors that facilitate and impede engagement in physical activity for individuals with a mood disorder. The intent was to understand the key features of a community based physical activity program for these individuals.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Exploring the perceptions from user’s perspectives is essential for understanding the effectiveness of an intervention, in congruences with the principle of CBPA, everything begins from the stakeholder’s perspectives, which is a bottom-up approach. Findings in this study are in line with current literature, showing CBPA is able to address multi-faceted needs of community stakeholders including abused women (Krieger et al, 2002 ; Poleshuck et al, 2018 ; Sims-Gould et al, 2017 ; Yoshihama et al, 2012 ; Zhou et al, 2016 ). CBPA allows researchers and service providers to engage more deeply with participants, as their needs could be addressed more effectively and their concerns could be responded more appropriately.…”
Section: Discussionsupporting
confidence: 89%
“…Exploring the perceptions from user’s perspectives is essential for understanding the effectiveness of an intervention, in congruences with the principle of CBPA, everything begins from the stakeholder’s perspectives, which is a bottom-up approach. Findings in this study are in line with current literature, showing CBPA is able to address multi-faceted needs of community stakeholders including abused women (Krieger et al, 2002 ; Poleshuck et al, 2018 ; Sims-Gould et al, 2017 ; Yoshihama et al, 2012 ; Zhou et al, 2016 ). CBPA allows researchers and service providers to engage more deeply with participants, as their needs could be addressed more effectively and their concerns could be responded more appropriately.…”
Section: Discussionsupporting
confidence: 89%
“…The strategies described by providers as being helpful to promoting a sense of belonging emphasise the importance of ensuring a positive and inclusive initial experience, creating a safe and stigma-free environment, and providing opportunities to forge relationships that enable participants to feel supported and valued. The primary importance of these factors has been highlighted previously in a study exploring the views of participants with major depressive disorder in relation to the features considered ideal for PA programmes (Sims-Gould et al, 2017). Other research (Belza et al, 2008;Hartley and Yeowell, 2015) has indicated the value of culturally specific programmes involving participants from similar CALD backgrounds, making it easier for participants to feel safe and comfortable when participating in organised PA.…”
Section: Discussionmentioning
confidence: 95%
“…Improved mental illbeing and wellbeing may be mediated through psychosocial mechanisms that result from positive social interactions, outdoor activity, or feelings of accomplishment. 94,95 There may also be behavioral mechanisms linked to improved auto-regulation or sleep patterns for those engaged regularly in sport that positively influence mental health. (94) Similarly, improved cognitive performance may be a result of complex problem solving and spatial reasoning needed during sport performance.…”
Section: Research Priority 8: How Does Youth Sport Contribute To Mental Health?mentioning
confidence: 99%